Nursing care quality and post-operative wound infections - Kos, Marek; Dziewa, Agnieszka; Ksykiewicz-Dorota, Anna; Drop, Bartłomiej; Kos, Michał (Polish Journal of Public Health, 2016)
Introduction. The aim of the surveillance over infections is to define the critical points, lacks in knowledge or staff skills, as well as lack of equipment. It is aimed at preventing the same mistakes from being conducted all over again, instead of making those guilty suffer from consequences of their mistakes. Aim. The authors aimed at assessing the quality of nursing care procedures in terms of preventing post-operative wound infections. Materials and methods. The research was conducted in medical treatment, surgical and intensive care ward. A self-constructed questionnaire “Nursing care quality and prophylaxis of hospital-acquired infections” was used for the study. It was validated using the peer judges method. Results and conclusions. The highest nursing care coefficient was noted in county hospitals (=94.5%), while the lowest was noted in clinical hospitals ( =91.3%). It was concluded that there is a deficit in adherence to procedures related to post-operative wound treatment.